Principles of Leadership and Deliberation Principles of Islamic Education in the Qur'an, Sirah Nabawiyah and the Medina Charter - Hamdan Hamdan; Pasiska Pasiska; Rohimin Rohimin; Khairuddin Khairuddin (PT. Islamic Research Publisher, 2023)
This research will review the concepts of multicultural Islamic religious education more specifically on the principle of leadership, in this study it is more explorative on the verses of the Qur'an, Sirah Nabawiyah, and the Medina Charter, while the method in this study is qualitative research in the nature of library research. Multiculturalism of social life in Indonesia exists because it is not something that is made automatically, but the multiculturalism of society is nothing but formed because of the diversity that belongs to the Indonesian nation itself long before Indonesia's independence, that spirit begins to be united again because of one thing, namely the same destiny and the same location, namely being colonized by the nation. foreigners for so many years that a spirit of unity was formed to break free from the shackles of colonialism. To become an independent sovereign country.